Preparation and Characterization of Egg White Protein-Based Composite Edible Coating Containing Thymol Nanoemulsion - Huajiang Zhang; Afeng Wei; Rui Chuang; Lina Xu; Cuiping Han; Hanyu Li; Ning Xia (Foods)
In this study, thymol-loaded nanoemulsion (THYNE) was incorporated into a mixture of egg white protein and hyaluronic acid to prepare antibacterial biopolymer coatings. The oil phase of the nanoemulsion (NE) was prepared by mixing different mass ratios of thymol and corn oil. NE was formed using ultrasonic emulsification, and the physicochemical properties of the NE were investigated. When the content of thymol in the oil phase was 30%, the particle size reached a minimum of 107.93 nm, PDI was 0.167, and Zeta potential was −18.2 mV, and it remained kinetically stable after 4 weeks of storage at 4 °C. Based on this study, composite coatings containing 5%, 10% and 20% THYNE were prepared, and the rheological properties, microstructure, FTIR, release properties and antibacterial properties of the coatings were investigated. The results show that the coating solutions exhibited shear thinning behavior. With increasing THYNE content, the coating structure became loose and inhomogeneous. The release rate of THY in the coatings was greater in 95% ethanol–water solution than in deionized water. In addition, the coating solutions showed stronger antibacterial activity against Staphylococcus aureus than against Escherichia coli. The egg white protein-based composite coating containing THYNE developed in this study is expected to be an antibacterial material for food packaging with sustained release performance.